Upaya Indonesia Dalam Meningkatkan Ekspor Udang Indonesia ke Amerika Serikat Periode 2017 - 2019 - Achmad Rayhan Iskandar, (2022)
Shrimp is one of the leading exports in fishery products for Indonesia to the United States market. The United States as the main destination for shrimp commodity exports can be profitable and become a source of foreign exchange for Indonesia. In 2017 Indonesian shrimp exports experienced obstacles to the United States market, this was because the United States through the National Oceanic and Atmospheric Administration (NOAA) imposed a policy of limiting the use of fishing nets (bycatch) for the fisheries sector to be exported to the United States. This study aims to determine the efforts made by Indonesia in increasing shrimp exports to the United States. The researcher uses international trade theory to see Indonesia in conducting international trade cooperation with the United States through the export of Indonesian shrimp to the United States. Then the researcher uses the concept of national interest, this concept is used to see the efforts made by Indonesia in increasing shrimp exports to the United States to meet its national interests in the country's economic sector. The researcher also uses the concept of protectionism, the concept of protectionism is used to see the efforts of the United States to protect its domestic market so that it can be seen whether the United States protects its domestic market or not. The use of qualitative research methods with a case study approach was chosen by the researchers to describe the efforts made by Indonesia to increase shrimp exports to the United States due to barriers to limiting the use of fishing nets (bycatch). The results of this study indicate that the efforts made by the Government of Indonesia have succeeded in increasing Indonesian shrimp exports to the United States. The efforts made by the Indonesian government are the Indonesian government holding a meeting with stakeholders, the Indonesian government holding a meeting with NOAA, the Indonesian government submitting a registration for shrimp exports to the United States, and the Indonesian government meeting with NOAA through Seafood Expo North America (SENA). Keywords: International Trade, Export, Shrimp, Indonesia, United States